Pengaruh Bermain Alat Musik Perkusi Terhadap Kecerdasan Musikal Pada Anak Kelompok A Di Kb-Ra/Tk Al-Islam 1 Jamsaren SurakartaTahun Ajaran 2016/ 2017 - Fatmawati, Nofi; Drs. Ilham Sunaryo, Drs. Ilham Sunaryo M.Pd (2017)
The purpose of the research was to determine the effect of playing the percussion instruments to the musical ntelligence group A of children in KB-RA/TK Al-Islam 1 Jamsaren Surakarta in academic year 2016/2017. The method of the research using a quantitative method there are using a kind of experimental research with pre-eksperimental research design is using one group pretest-posttest design. This research was conducted in KB-RA/TK Al-Islam 1 Jamsaren Surakarta. Subject of the research were children in group A in KB-RA/TK Al-Islam 1 Jamsaren Surakarta with the amount of 25 children. Data collection techniques of the research were conducted through observastion, there are nonparticipant observation and documentation. Data analysis techniques of the research using ttest with SPSS 16.0 for windows. The results of data analysis using ttest obtained thitung -16.613 ≤ ttabel -2.064 so H0 rejected and Ha accepted which means there is the influence of playing the percussion instruments to the musical intelligence. Keyword: Playing the percussions instruments, musical intelligence